Research of the optimal design of a jet pump for regulating a Pelton hydro turbine - Liamasov A.K.; Denisov K.E.; Biriulin M.A. (E3S Web of Conferences, 2024)
Hydroelectric power plants (HPP) contribute a significant share to electricity generation in Russia. Considering the prospects for the development of this sector and using the hydropower potential, it is necessary to explore methods for the modernization of hydroelectric power plants. This article explores a new method of regulating active turbines (Pelton) based on altering the nozzle flow rate by using a jet pump that operates with used fluid from the runner. The relevance of this solution lies in the potential to increase the operational lifespan of high-head pumped storage hydroelectric power plants (PSHPP) and enhance reliability by eliminating or reducing the intensity of the regulatory needle's operation in the guide vane mechanism. Based on the hydraulic scheme incorporating the jet pump into the hydroelectric power plants penstock upstream of the guide apparatus, several geometric configurations of the jet pump were evaluated using CFD modeling to assess the energy losses associated with the proposed regulation method.